Economic analysis of athletic team coverage by an orthopedic practice. Issue 4 (2nd October 2015) - Lombardi, Nicholas; Freedman, Kevin; Tucker, Brad; Austin, Luke; Eck, Brandon; Pepe, Matt; Tjoumakaris, Fotios
Abstract: Objective: Coverage of high school football by orthopedic sports medicine specialists is considered standard of care in many localities. Determining the economic viability of this endeavor has never been investigated. The primary purpose of the present investigation was to perform an economic analysis of local high school sports coverage by an orthopedic sports medicine practice. Methods: From January 2010 to June 2012, a prospective injury report database was used to collect sports injuries from five high school athletic programs covered by a single, private orthopedic sports medicine practice. Patients referred for orthopedic care were then tracked to determine expected cost of care (potential revenue). Evaluation and management codes and current procedure terminology codes were obtained to determine the value of physician visits and surgical care rendered. Overhead costs were calculated based on historical rates within our practice and incorporated to determine estimated profit. Results: 19, 165 athletic trainer contacts with athletes playing all sports, including both those 'on-field' and in the training room, resulted in 473 (2.5%) physician referrals. The covering orthopedic practice handled 89 (27.9%) of the orthopedic referrals. Of orthopedic physician referrals, 26 (5.4%) required orthopedic surgical treatment. The covering team practice handled 17/26 (65%) surgical cases. The total revenue collected by the covering team practice was $26, 226.14. The overhead cost of treatment was $9441.41. Overall estimated profit of orthopedic visits and treatment during this period for the covering practice was $16, 784.73. Conclusions: The covering team practice handled 28% of the orthopedic referrals, 65% of the surgical cases and captured 59% of the potential profit. An increase in physician referrals could increase the benefit for orthopedic surgeons.